ANALISIS KUALITAS PELAYANAN PEMBUATAN SERTIFIKAT TANAH DI KANTOR PERTANAHAN KABUPATEN BOYOLALI - Taufik Zaenal Abidin; Moch. Mustam; Dyah Lituhayu; Hardi Warsono (Journal of Public Policy and Management Review, 2016)
The success of a government can be seen from the quality of service that the government give to the people. The level of quality of service depends on the performance of the bureaucracy as public service providers. In order to improve services and to develop Boyolali District, the government of Boyolali District create Land Office services that obliged to carry out registration of land in Boyolali. Only 68,05% land in Boyolali District has registered in the Land Office. Many people has complained because the lack of service that the Land Office give. The purpose of this research is to find out the quality and the factors that affect the services in Boyolali District Land Office. The assesment of quality service is measured by three (3) components, interpersonal environment, procedure and technical environment, and then using five (5) dimensions: tangible, reliability, responsiviness, assurance and empathy. This research used qualitative descriptive approach, Boyolali District Land Office employee as the informan and the people who makes the land certificate. The results of this research showed the three components (officers, procedures and techniques) were measured by using five dimensions namely tangible, reliability, responsivness, assurance and empathy still require some improvement and some of the dimensions that must be maintained. The factors that affect the quality of service is awareness, regulations / standards, organization, personnel skills and infrastructure. Advice can be given to improved officer quality is increase the number of field officers and provide training. Land Office have to socialize all the programs so the users can understand the procedures, and then optimize the use of cars Larasita, a clear schedule, supervise the officers and provide queue number machine.